2006
DOI: 10.1017/s0950268806006418
|View full text |Cite
|
Sign up to set email alerts
|

Social mixing patterns for transmission models of close contact infections: exploring self-evaluation and diary-based data collection through a web-based interface

Abstract: Although mixing patterns are crucial in dynamic transmission models of close contact infections, they are largely estimated by intuition. Using a convenience sample (n=73), we tested self-evaluation and prospective diary surveys with a web-based interface, in order to obtain social contact data. The number of recorded contacts was significantly (P<0.01) greater on workdays (18.1) vs. weekend days (12.3) for conversations, and vice versa for touching (5.4 and 7.2 respectively). Mixing was highly assortative wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
155
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(165 citation statements)
references
References 12 publications
6
155
2
Order By: Relevance
“…Different diseases require different levels of contact between individuals to effect transmission (Beutels et al 2006). Meningitis and smallpox, for example, are thought to normally require very close contact between individuals to cause infection, while influenza and measles are thought to transmit more easily via airborne droplets and therefore may only require con-versational proximity between individuals to transmit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different diseases require different levels of contact between individuals to effect transmission (Beutels et al 2006). Meningitis and smallpox, for example, are thought to normally require very close contact between individuals to cause infection, while influenza and measles are thought to transmit more easily via airborne droplets and therefore may only require con-versational proximity between individuals to transmit.…”
Section: Discussionmentioning
confidence: 99%
“…Social networks have been documented in the sociological literature, but are generally inappropriate for epidemiological purposes. Definitions of contacts that do not correlate closely with transmission opportunities, such as relationship-based definitions, inclusion of remote (letter, telephone or e-mail) interactions or the measurement of a particular subset of social contacts, render many such studies unsuitable from the epidemiological perspective (de Sola Pool & Kochen 1978;Bernard et al 1990;Wasserman & Faust 1994;Dunbar & Spoors 1995;Beutels et al 2006). As a consequence, there is relatively little available information about the patterns of human social interactions relevant to the transmission of many infectious diseases (Edmunds et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Methods have been developed to measure potentially contagious contacts in realworld settings. Currently, the dominant approach for measuring epidemiologically relevant contact data is contact diaries [6][7][8][9][10][11][12]. Empirical research on potentially contagious contacts, particularly the highly cited study by Mossong et al [8], has influenced the discussion on the patterns and risk factors of disease spread and has informed infectious disease modelling [e.g.…”
Section: Introductionmentioning
confidence: 99%
“…One study compared retrospective and prospective study designs and found 'only minor differences in the number of contacts, with on average more contacts reported in the prospective survey ' [7, p. 133]. Another study compared a web-based mode of data collection with a diary-based one and concluded that the diary-based approach is less demanding and better suited for collecting detailed data than the web-based approach [9]. A similar result was reported in a study that compared paper-based diaries with data collection via personal digital assistants (PDAs) [10].…”
Section: Introductionmentioning
confidence: 99%
“…The mean value of potentially contagious contacts can be interpreted in a meaningful way, since the distribution of daily contacts is unimodal with a clear "typical" number of contacts [12][13][14][15]. Potentially dominant properties of the underlying contact structure are the clustering of such contacts and their repetitiveness, i.e.…”
Section: Introductionmentioning
confidence: 99%